Magnetic nanostickers for active control of interface-enhanced selective bioadhesion - Changshun Hou; Junjia Guo; Bonan Sun; Kai Fung Chan; Xin Song; Li Zhang (Nature Communications)
Abstract Natural biological tissues exhibit different mechanical and surface properties. These disparate features make their connections with engineering materials quite difficult due to the lack of universal methods for tuning the interfacial bonding over a wide range. However, the precise control of interfacial properties, including modulus and adhesion on diverse biological tissues, requires overcoming multiple inherent and external barriers. Here we propose an interface-enhanced strategy by spatial and temporal anchoring of magnetic nanostickers for controlled bioadhesive properties. Fully exploiting the interactions from nanostickers by remote control enables the attached patch to achieve extremely high adhesion energy ( ~ 1250 J m-2) and interfacial fatigue resistance with a threshold of ~50 J m-2, at a very low area density of nanostickers (4 μg/mm2). The controlled interfacial properties as well as space and time for anchoring, lead to comprehensively tunable bioadhesion on diverse tissues such as skin, intestine, liver, and kidney, which are strongly desired in biomedical applications. Integration with fragile tissues in female Sprague-Dawley rats for 10 days further demonstrates that the anchored biointerface can adapt to the in vivo environment and promote postoperative recovery. The biointerface bridged by intelligent nanostickers prompts the methodology for bioadhesion towards controllable orientation.